2012
DOI: 10.1093/jpepsy/jss072
|View full text |Cite
|
Sign up to set email alerts
|

The Suicidal Feelings, Self-Injury, and Mobile Phone Use After Lights Out in Adolescents

Abstract: Mobile phone use after lights out may be associated with poor mental health, suicidal feelings, and self-injury in both early and late adolescents. Association between reduced sleep and the mobile phone use was confined to early adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
57
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 25 publications
9
57
2
7
Order By: Relevance
“…More recent studies regarding adolescents' bedtime mobile phone use include two surveys conducted in Japan examining the relation of mobile phone communication after lights out with sleep (Munezawa et al 2011;Oshima et al 2012). Munezawa et al (2011) found both texting and calling after lights were turned off to be related with more sleep disturbance (including short sleep duration, subjective poor sleep quality, excessive daytime sleepiness, and insomnia symptoms) controlling several confounders (including gender, grade-level, alcohol-drinking, smoking, eating breakfast, extracurricular activities, and mental health).…”
Section: Electronic Media Use and Adolescents' Sleepmentioning
confidence: 99%
“…More recent studies regarding adolescents' bedtime mobile phone use include two surveys conducted in Japan examining the relation of mobile phone communication after lights out with sleep (Munezawa et al 2011;Oshima et al 2012). Munezawa et al (2011) found both texting and calling after lights were turned off to be related with more sleep disturbance (including short sleep duration, subjective poor sleep quality, excessive daytime sleepiness, and insomnia symptoms) controlling several confounders (including gender, grade-level, alcohol-drinking, smoking, eating breakfast, extracurricular activities, and mental health).…”
Section: Electronic Media Use and Adolescents' Sleepmentioning
confidence: 99%
“…[ Figure 2 박증 (Im, Hwang, Choi, Seo, & Byun, 2013;Kim et al, 2013;Lee et al, 2013;Lemola et al, 2014), 자살관련 행태 (Oshima et al, 2012;Wang et al, 2014 …”
Section: 연구 대상집단mentioning
confidence: 99%
“…6 A study published in 2012 found a significant association between nocturnal mobile phone use and poor mental health, suicidal feelings and self-harm after controlling for other confounding variables (including sleep length) in 17,920 adolescents. 7 Despite evidence demonstrating an increase in the use of electronic media and smartphones in AYAs, as well as evidence linking this increased use to sleep and mood disturbances, studies looking at smartphone use, sleep disturbance and chronic pain disorders in AYAs are lacking. This is an area that warrants further investigation.…”
Section: Sleep In Adolescents and Young Adultsmentioning
confidence: 99%